Incorportaion of primary amines into a polyester chain by a combination of chemical and lipase-catalyzed epsilon-caprolactone ring-opening processes - MARZORATI, MATTIA; B. Danieli; K. Hult; S. Riva (Advanced Synthesis & Catalysis, 2007)
A simple chemoenzymatic strategy for the incorporation of bioactive and suitably functionalized molecules into a polyester chain has been developed. The protocol involves first the reaction of a primary amine with -caprolactone to give an amide carrying a terminal primary hydroxy group, followed by the enzymatic growth of the polymeric chain triggered by Novozym 435. This method is versatile and easy to handle and is suitable for the incorporation of different amines into polyesters, as has been shown with the model compounds benzylamine and tryptamine, the bioactive compound N-deacetylthiocolchicine and the functionalized propargylamine and tyramine .